The China society yearbook : analysis and forecast of China's social development. Volume 3 - Ru, Xin; Lu, Xueyi; Li, Peilin (Chinese Academy of Social Sciences yearbooks. Society ;, 2009)
The 2008 volume of The China Society Yearbook, the third volume in the annual China Society Blue Book series to be translated into English, contains important statistics and analysis from Chinese scholars on a wide array of social issues in China. Topics explored in this volume include employment, social security, national health insurance, labor security, political participation, the internet, food safety, corruption, and quality of life.